CONCEPTUAL STUDY OF FORMATION OF BLOOD CELLS FROM TISSUE NUTRITIONAL LAWS WITH ITS CLINICAL IMPACT- AN AYURVEDIC PERSPECTIVE (International Journal of Ayurveda and Pharma Research, 2019)
Rakta Dhatu is the main source for life longevity and survival of human beings. Formation of Rakta Dhatu is a continuous process. The heterologous food after the action of bio-energies (Agni) in digestion phase is converting into homologous form. Agni-bala (strength of bio-energies) are main helping hand for 2nd Dhatu i.e. Rakta Dhatu (blood cells) in the metabolic action of the body. Further the bio-energies works with changing need of the essence part as absorption and metabolism are started so that generation of tissues (Dhatus) occurs smoothly in the body. The Dhatu Siddhanta (tissue forming laws) in which theories of tissue formation and tissue differentiation were mentioned. The Ahara Rasa (Productive essence part) with the help of different bio-energies in different areas in body helps to produce tissues (Dhatus). To understand how the tissues are formed it is necessary here to understand the logics of Ayurvedic concepts or Siddhanta that proves the formation of Dhatu from Ahara Rasa. The modern science explains the formation of blood cells in embryonic stage by the help mesenchymal cells. The applied aspect of this work is to prevent disorders before their manifestations occurs in the human body. Various diseases that occur due to many causative agents are like- food/Ahara or Agni-Bala (strength of bio-energies), getting poor food digestion or metabolism. On the Ahara ground many different type of etio-pathogenis are aroused due to malfunctioned food or due to malabsorption (Dhatuagnivikriti) that may leads to Dhatuagninasana (metabolic dysfunction). To understand deeply we have to go step by step the physiological ground of food digestion, its laws and how the blood tissues are formed from the sciences, applied aspects of Dhatu Nirmana and its vitiated factors.